Quantification of Longevity Risk for Pension Insurance in V4 countries - Gogola, Ján (My University, 2017)
Longevity risk, the risk that people will live longer than expected, weighs heavily on those who run pension schemes and on insurers that provide annuities. Hence the prediction of future mortality rates is an issue of fundamental importance for the insurance and pensions industry. Our analysis focuses on mortality at higher ages (65 – 95), given our interest in pension-related applications where the risk associated with longer-term cash flow is primarily linked to uncertainty in future rates of mortality. We use data on deaths and exposures for the The Visegrad Group (V4) – the Czech Republic, Poland, Hungary and Slovakia from the Human Mortality Database (HMD). We have shown that if the today rate of increase will continue, it will at age 65 concluded (after calculation) to increase the present value of pension liabilities in defined-benefit schemes about 5% if we use cohort life table instead of period life table.
Kvantifikace vlivu rizika dlouhověkosti pro penzijní pojištění v zemích V4
Keywords: longevity risk, annuity, stochastic mortality, life table, Lee-Carter model; riziko dlouhověkosti, anuita, stochastická úmrtnost, úmrtnostní tabulka, Lee-Carterův model